2009
DOI: 10.1039/b907726j
|View full text |Cite
|
Sign up to set email alerts
|

A theobromine derived silver N-heterocyclic carbene: synthesis, characterization, and antimicrobial efficacy studies on cystic fibrosis relevant pathogens

Abstract: The increasing incidence of multidrug-resistant (MDR) pulmonary infections in the cystic fibrosis (CF) population has prompted the investigation of innovative silver based therapeutics. The functionalization of the naturally occurring xanthine theobromine at the N1 nitrogen atom with an ethanol substituent followed by the methylation of the N9 nitrogen atom gives the N-heterocyclic carbene precursor 1-(2-hydroxyethyl)-3,7,9-trimethylxanthinium iodide. The reaction of this xanthinium salt with silver acetate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 19 publications
3
62
0
1
Order By: Relevance
“…The research presented herein provides alternatives to some of the products on the market, to widen the spectrum of microbial pathogens susceptible to silver and also to target organisms which are resistant to current silver complexes [2][3][4][5][6] and for other biological properties [7].…”
Section: Introductionmentioning
confidence: 99%
“…The research presented herein provides alternatives to some of the products on the market, to widen the spectrum of microbial pathogens susceptible to silver and also to target organisms which are resistant to current silver complexes [2][3][4][5][6] and for other biological properties [7].…”
Section: Introductionmentioning
confidence: 99%
“…designed a library of N -heterocyclic silver carbene complexes (SCCs), which improved the stability of Ag + to light and aqueous solution, allowed for the direct administration of silver-compounds via nebulization, and demonstrated the antimicrobial activity of Ag + against contemporary Gram-positive and Gram-negative pathogens. 1624 In parallel, Cannon and Youngs et al demonstrated sustained silver release and potent in vitro and in vivo antimicrobial efficacy of SCC10-bearing L-tyrosine polyphosphate nanoparticles (LTP NPs) against the cystic fibrosis pathogen Pseudomonas aeruginosa . 25 Meanwhile, benefiting from polymeric backbone-structured building blocks with precisely controlled architectures, surface characteristics and supramolecular assembly, 26, 27 Cannon, Youngs and Wooley et al highlighted the preparation of smaller particle size and the introduction of functionalities for attachment of targeting moieties by utilizing multifunctional shell cross-linked knedel-like polymeric nanoparticles (SCK NPs) of poly(acrylic acid)- block -polystyrene (PAA- b -PS).…”
mentioning
confidence: 99%
“…8 More recent efforts aimed at improving the modest water solubility of complex 2. For this purpose, theobromine rather than caffeine has been introduced as a basic structural motif, 9 since the unsubstituted nitrogen N1 in theobromine 90 allows for incorporating functional groups that increase the solubility of the silver complex in water. Insertion of an ethanol residue in theobromine, followed by nitrogen N9 alkylation and subsequent metalation affords the silver NHC complex 3.…”
mentioning
confidence: 99%